Sosialisasi Pengolahan Pupuk Organik Cair (POC) dari Limbah Rumah Tangga di Desa Tejo - Roziqin, Muhamad Khoirur; Agus Suhadi; Dwi Febriani Saputri; M. Musyapa Ali; Melyvita Nur Angraeni; Saiful Anwar (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2024)
Agriculture is something that cannot be separated from the lives of Indonesian people where most of the people are farmers. More specifically, the people of Tejo village are mostly farmers who make a living, therefore fertilizer is their daily companion. Most farmers in Indonesia still depend on the use of inorganic or chemical fertilizers even though excessive use of inorganic fertilizers in the long term will actually cause negative effects. The application of excessive doses of synthetic chemical fertilizers can cause environmental pollution, moreover, continuous use for a long time can cause land productivity to decrease and soil fertilizing microorganisms to decrease. One of the non-chemical fertilizers that can be used is organic fertilizer in liquid form (POC) from onion peel waste and rice washing water where the excess more quickly stimulates the growth of roots, new shoots and plant cells, repairs chlorophyll in leaves, strengthens pollen stalks in flowers, and strengthens endurance in plants. From the results of the recapitulation of the Pre-test questionnaire, 56% increased by 33% with the socialization to 86% of the results of the recapitulation of the Post-test questionnaire.